Table Tennis Ball Launcher - M Haris Satria; Bangkit Seandi Taroreh; Nina Paramita; Dominggus Mirop (UNIB Press, 2022)
The learning of the table tennis course is a practical course where the characteristics are unique so that mastery of basic techniques is highly dependent on doing more repetitions. The correct movement will appear along with the automation of the motion. The purpose of the research and development of this table tennis throwing device is to (1) develop a table tennis throwing tool for the process of implementing table tennis learning, (2) obtain empirical data about the feasibility of the table tennis throwing tool that has been developed. The ultimate goal of this development research is to produce a product in the form of learning media, namely a table tennis ejection tool that can provide meaningful movement experiences and can help improve basic technical skills to the ability to play table tennis. The method used Research and Development (R&D) methods from Borg and Gall. The research subjects are college students of Sports Education at Universitas Bina Darma. Instrument test used observation and questionnaires. Data analysis techniques were carried out with qualitative and quantitative approaches. This product is produced through the research and development stage. The resulting product is a table tennis ball. Based on the product trial analysis phase, the resulting product answers the needs and becomes a solution for lecturers and students in the implementation of table tennis course learning. Based on the results of validation tests, instrument reliability tests, small group try-out and field try group, this table tennis ejection tool is feasible and can be used in learning table tennis theory and practice courses.